Antimicrobial Potential of Actinomycetes Isolated from Soil of Nepal - Pant, Krishna Prasad; Bohara, Madan Singh; Shah, Yogendra; Acharya, Amrit; Sharma, Supriya; Lekhak, Binod (Far Western Review, 2025)
Antimicrobial resistance (AMR) to antibiotics is increasing rapidly, which is a serious public health problem worldwide, so the issue of AMR should be addressed in time. Many studies have been conducted in Nepal to isolate potent Actinomycetes strain from soil and water in various parts of the country. The aim of this review is to find novel Actinomycetes isolates from Nepal producing bioactive compounds capable of suppressing the growth of multidrug-resistant pathogens. Preliminary screening in these studies in Nepal have identified isolates with notable antimicrobial activity against various pathogenic bacteria including Escherichia coli, ESBL E. coli, Staphylococcus, MRSA, Enterococcus faecalis, Klebsiella pneumoniae, Bacillus subtilis, Pseudomonas aeruginosa, Acinetobacter baumannii, Salmonella Typhi and others. Findings from several studies in Nepal indicate that Actinomycetes isolated from different habitats of Nepal can produce a wide array of bioactive compounds like diketopiperazines, actinomycins, bacterial alkaloids, anthramycin-type antibiotics, lipase inhibitors, cytocidal metabolites, antifungal and antitumor antibiotics. In conclusion various regions across Nepal contain novel Actinomycetes strains that can produce novel bioactive compounds and effective antimicrobial drugs to combat the growing problem of AMR.